Esophageal pressure monitoring and its clinical significance in severe blast lung injury - Shao, Shifeng; Wu, Zhengbin; Wang, Yi; Wang, Yaoli; Wang, Zhen; Ye, Huan; Zhao, Hui (Frontiers in Bioengineering and Biotechnology, 2024)
The incidence of blast lung injury (BLI) is escalating annually due to military conflicts and industrial accidents. Currently, research into these injuries predominantly utilizes animal models, yet there remains a scarcity of studies focused on monitoring respiratory mechanics post-BLI, despite the availability of various models. Consequently, our objective was to develop a model for monitoring esophageal pressure (Pes) following BLI using a biological shock tube (BST), aimed at providing immediate and precise monitoring of respiratory mechanics parameters post-injury.Methods: Six pigs were subjected to BLI using a BST, during which Pes monitoring was conducted. We assessed vital signs, conducted blood gas analysis, hemodynamics evaluations, lung ultrasound, and measured respiratory mechanics before and after the inflicted injury. Furthermore, the gross anatomy of the lungs three hours post-injury was examined, and hematoxylin and eosin staining was conducted on the injured lung tissues for further analysis.The experimental section of the BST reached a pressure of 402.52 ± 17.95 KPa with a peak pressure duration of 53.22 ± 1.69 ms. All six pigs exhibited an anatomical lung injury score ≥3, and pathology revealed classic signs of severe BLI.Post-injury vital signs showed an increase in HR and SI, along with a decrease in MAP (p<0.05). Blood gas analyses indicated elevated levels of Lac, CO2-GAP, A-aDO2, HB, HCT, and reduced DO2, OI, SaO2, and OER (p<0.05). Hemodynamics and lung ultrasonography findings showed increased ELWI, PVPI, SVRI, and lung ultrasonography scores, and decreased CI, SVI, GEDI and ITBI (p<0.05). Analysis of respiratory mechanics revealed increased Ppeak, Pplat, Dring P, Map, PEF, Ri, lung elastance, MP, Ptp, Ppeak-Pplat, and ΔPes, while Cdyn, Cstat, and time constant were reduced (p<0.05).We have successfully developed a novel respiratory mechanics monitoring model for severe BLI. This model is reliable, repeatable, stable, effective, and user-friendly. Pes monitoring offers a non-invasive and straightforward alternative to blood gas analysis, facilitating early clinical decision-making. Our animal study lays the groundwork for the early diagnosis and management of severe BLI in clinical settings.